Pemanfaatan Bahan Organik Sebagai Solusi Solum Tanah Dangkal di Desa Slateng Kecamatan Ledokombo Kaki Gunung Raung - Vega Kartika Sari; Marga Mandala; Basuki Basuki (Universitas Mataram, 2022)
Slateng village is located at the western foot of Mount Raung in Ledokombo District, Jember Regency. Farming and cattle ranching provide the majority of the people's income. Agricultural land productivity is still low compared the production standard based on plant variety descriptions. The cultivated land has shallow solum. This activity aims to provide training for Slateng’s farmer to boost cultivated plant yield by enhancing the properties of shallow solum soil and producing organic fertilizer from agricultural waste. Socialization and practice are the methods employed for this activity. The increased of participants' knowledge grew from 30% to 100% as a result of the exercise. Participants were quite interested with the training on creating organic fertilizers, which required active participation from participants, particularly farmers, with a satisfaction rate of 90%. This community service activities can help increase the production of cultivated plants, particularly on marginal land with shallow solum soil.